Efficacy and safety of Ixazomib-based maintenance therapy after autologous hematopoietic stem cell transplantation in multiple myeloma patients: a retrospective analysis - Chen, Mengyuan; Chen, Gang; Xu, Jianli; Zhang, Kaile; Yang, Ruixue; Han, Chunxia; Hou, Jia; Jiang, Ming; Yuan, Hailong (Frontiers in Medicine, 2026)
IntroductionThe therapeutic standard for post-autologous stem cell transplantation (ASCT) maintenance in multiple myeloma (MM) is evolving, with daratumumab-based regimens emerging as highly effective. However, access to such therapies remains limited in regions like China. This study evaluated the real-world efficacy and safety of the oral proteasome inhibitor ixazomib as a practical alternative for maintenance therapy in this setting.MethodsThis single-center, retrospective analysis included 28 MM patients who received ixazomib-based maintenance (monotherapy or combination) for ≥5 months after ASCT (from a total cohort of 64 ASCT recipients) between August 2019 and August 2023. Treatment was assigned based on mSMART 3.0 risk stratification and adjusted per clinical circumstances. The primary endpoint was progression-free survival (PFS). Secondary endpoints included treatment response, minimal residual disease (MRD) status, and safety.ResultsThe median age of the patients was 57 years (range: 48–69). Before ASCT, 9 patients (32.1%) achieved complete response (CR), 7 (25.0%) achieved very good partial response (VGPR), and 12 (42.9%) achieved partial response (PR). After ASCT, responses deepened: 17 patients (60.7%) achieved CR, 6 (21.4%) VGPR, and 5 (17.9%) PR. Following Ixazomib maintenance, 15 patients (53.5%) were in CR, 8 (28.6%) in VGPR, and 5 (17.9%) in PR. Four patients experienced disease progression during follow-up. The incidence of grade ≥ 3 adverse events was 3.6%. The estimated 3-year PFS and overall survival rates were 70.8% (95% CI, 52.18%–89.42%) and 87.4% (95% CI, 73.88%–100.92%), respectively. Notably, patients who sustained MRD negativity for over 1 year had an estimated 3-year PFS of 100%, significantly higher than that of MRD-positive patients.DiscussionWithin the constraints of the current Chinese clinical context, ixazomib-based maintenance therapy demonstrates favorable efficacy and a manageable safety profile for MM patients after ASCT, offering a viable and accessible alternative. Achieving sustained MRD negativity is critically important for long-term outcomes, reinforcing its value as a key treatment goal. These real-world findings support the role of ixazomib, particularly for patients ineligible for or intolerant to standard regimens.